The Effect of E-Service Quality Mediated by Customer Satisfaction, Perceived Value, Customer Engagement, and Brand Image on Lazada Indonesia's Customer Loyalty - Kevin Nicholas Valentino; Steven Raharjo (iBuss Management, 2023)
This study seeks to objectively investigate the factors influencing Lazada Indonesia's customer loyalty in the country's rapidly expanding e commerce sector. Despite having spent lots of money and investment, Lazada Indonesia was still not the top e-commerce platform in Indonesia, falling behind Tokopedia and Shopee. Thus, the links between brand image, perceived value, customer satisfaction, customer engagement, and e-service quality are investigated and discussed. This study uses a non-probability sampling through convenience sampling technique with 148 respondents collected, while the validity and reliability confirmation process are using the PLS SEM method. Likert scale will also be used within this study. The result is that the path coefficient of most marketing constructs remains significant while the outliers are from brand image towards customer satisfaction, brand image towards customer loyalty, customer satisfaction towards customer loyalty, e-service quality towards brand image, e-service quality towards customer loyalty, and perceived value towards customer satisfaction. For the mediation analysis, this research resulted in complementary mediations, full mediations, and no mediations. The result of this study confirmed that there is a significant effect of several marketing constructs. This research also finds an inverse relation finding means an increase in customer engagement when customer satisfaction is low.Keywords: E-service quality, Customer satisfaction, Customer engagement, Customer loyalty, Perceived value, Brand image.